2019
DOI: 10.1111/add.14795
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adding the community reinforcement approach to motivational enhancement therapy for adults aged 60 years and older with DSM‐5 alcohol use disorder: a randomized controlled trial

Abstract: Aim To examine whether adding the Community Reinforcement Approach for Seniors (CRA‐S) to Motivational Enhancement Therapy (MET) increases the probability of treatment success in people aged ≥ 60 years with alcohol use disorder (AUD). Design A single blind multi‐centre multi‐national randomized (1 : 1) controlled trial. Setting Out‐patient settings (municipal alcohol treatment clinics in Denmark, specialized addiction care facilities in Germany and a primary care clinic in the United States). Participants Betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 38 publications
6
42
0
8
Order By: Relevance
“…The study was conducted by research centers in 3 countries (Denmark, United States, and Germany) between 2014 and 2016. In the current paper, only baseline data from the Danish sites were used (Andersen et al, 2020). Details and results of the Elderly Study can be found in Andersen et al (Andersen et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted by research centers in 3 countries (Denmark, United States, and Germany) between 2014 and 2016. In the current paper, only baseline data from the Danish sites were used (Andersen et al, 2020). Details and results of the Elderly Study can be found in Andersen et al (Andersen et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in this retrospective study among adults aged 60–70, with different alcohol use behavior, we aimed to: (1) describe and analyze use of health care over the past 15 years, grouped by current alcohol use behavior, and (2) identify the most common prior morbidities as causes for hospital contacts, and the burden of disease over 15 years in this age group, grouped by current alcohol use behavior. We combined data from 2 studies: the Danish part of the international randomized trial, the Elderly Study (Andersen et al, 2020) (inclusion 2014–2016), and a sub‐sample of the participants in the Danish National Health Survey 2013 (DNHS 2013). The rationale for combining data from the trial with survey data was to include individuals suffering from AUD and seeking treatment, a group typically much under‐represented in surveys (Christensen et al, 2015; McMinn et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, no studies on MET for substance use included OA ≥62 years. This multinational study compared MET (4 sessions) and MET plus a community reinforcement approach (up to 8 additional sessions) to reduce alcohol use among just under 700 adults ≥60 years [66]. At the 26-week follow-up, half of the participants in both groups (48.9 and 52.3%, respectively) were abstinent or maintained low blood alcohol concentration.…”
Section: Interventionmentioning
confidence: 99%
“…This study is a secondary analysis of data from the Elderly Study; a multisite, randomized controlled clinical trial that examined and compared 2 psychosocial interventions aimed at treating AUD among 60+‐year‐old individuals (Andersen et al, 2020; Andersen et al, 2015). There was no control group that did not receive treatment.…”
Section: Methodsmentioning
confidence: 99%